(untitled) (Journal of Foreign Language Studies, 2024)
Sound and adequate learning outcome assessment (LOA) in teaching and learning foreign languages for tourisms purposes would generate motivation for students at tourism colleges in learning foreign languages. The article discusses fundamental issues of assessing tourism college students’ foreign language learning outcome with the competency - based approach. It also provides practical suggestions of the implementation of such new assessment method, and regarded as a useful reference source for tourism colleges in their continuous improvements of training quality and effectiveness, towards helping their graduates meet both Vietnam and ASEAN standards.